2017
DOI: 10.1002/dneu.22492
|View full text |Cite
|
Sign up to set email alerts
|

Volume and density of microglomeruli in the honey bee mushroom bodies do not predict performance on a foraging task

Abstract: The mushroom bodies (MBs) are insect brain regions important for sensory integration, learning, and memory. In adult worker honey bees (Apis mellifera), the volume of neuropil associated with the MBs is larger in experienced foragers compared with hive bees and less experienced foragers. In addition, the characteristic synaptic structures of the calycal neuropils, the microglomeruli, are larger but present at lower density in 35-day-old foragers relative to 1-day-old workers. Age- and experience-based changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 97 publications
(142 reference statements)
2
12
0
Order By: Relevance
“…In fruit flies, visual reversal learning has also been shown to be improved by GABAergic inhibition [ 54 ], suggesting that sparse coding might be beneficial to solve this task. In honey bees, the density of synaptic boutons in the collar was not related to performance in a 2-colour discrimination task [ 55 ], but bumblebees with a high density of synaptic boutons in the collar have been shown to learn faster to discriminate between 10 different colours [ 56 ]. A possibility might be that increasing number of synaptic boutons in honey bees with greater experience might facilitate some learning tasks (not tested here) to the expense of others (such as reversal learning).…”
Section: Discussionmentioning
confidence: 99%
“…In fruit flies, visual reversal learning has also been shown to be improved by GABAergic inhibition [ 54 ], suggesting that sparse coding might be beneficial to solve this task. In honey bees, the density of synaptic boutons in the collar was not related to performance in a 2-colour discrimination task [ 55 ], but bumblebees with a high density of synaptic boutons in the collar have been shown to learn faster to discriminate between 10 different colours [ 56 ]. A possibility might be that increasing number of synaptic boutons in honey bees with greater experience might facilitate some learning tasks (not tested here) to the expense of others (such as reversal learning).…”
Section: Discussionmentioning
confidence: 99%
“…Van Nest et al . [ 28 ] found no correlation between microglomerular density in the mushroom body calyces and honeybee performance on a two-colour visual discrimination task. In our study, we found a statistically strong positive correlation between performance on a visual discrimination task and microglomerular density in the mushroom body calyxes, and specifically in the visual input region (collar region).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a statistically strong positive correlation between performance on a visual discrimination task and microglomerular density in the mushroom body calyxes, and specifically in the visual input region (collar region). The reason for the difference in sign of correlation (with [ 28 ]) and significance (with [ 29 ]) may be owing to the differences in controls, as we controlled for both age and prior foraging experience. In addition, the 10-colour Learning task in our experiment was arguably more difficult than the traditional Two-colour Learning task used by these other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with brood exposed workers ( pre-eclosion) also being affected this indicates exposure to be affecting synaptic development and proliferation in the calyces. For instance, microglomeruli configuration is considered to be associated with learning and memory in bees [73][74][75][76], and reduced density from neonicotinoid exposure has been reported in honeybees [35]. It could also stem from impeded neurogenesis where neuronal precursor cells were prevented from giving rise to mushroom body Kenyon cells, which in honeybees occurs during development pre-eclosion [77,78], or reduced Kenyon cell size as shown in neonicotinoid exposure experiments on bumblebee cell cultures [79].…”
Section: (A) Pesticide Exposure During Early Development Affected Resmentioning
confidence: 99%